UPAYA MENINGKATKAN KEAKTIFAN MENULIS MELALUI BELAJAR DI LUAR KELAS DENGAN METODE JOY FULL LEARNING - Ara Zuraeda (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
Students' understanding of learning to write is still low. The learning strategy used by the teacher is considered ineffective. To overcome this, there are active learning strategies and methods, including implementing learning strategies outside the classroom with the Joy Full Learning method. This can solve the problem of the low quality of learning. Learning strategies and methods emphasize the activeness and cooperation of students in solving problems. The purpose of this study was to describe the increase in the activity of class II students of MIN 1 Pangandaran in Indonesian, especially Writing through the application of natural strategies (outside the classroom.) With the Joy Full Learning method. The research design uses classroom action research that includes planning, implementation, observation and reflection. The results showed that the implementation of natural strategies (learning outside the classroom) with the Joy Full Learning method was proven to improve the quality of student learning outcomes in Indonesian Language Subjects at MIN 1 Pangandaran. The results of the assessment show that all students get satisfactory scores. Students say they are happy with this learning strategy and method, this is manifested by the growing sense of satisfaction being able to express their emotions, the classroom atmosphere becomes more lively and there are new experiences for students to carry out a simple analysis of problems that are arising within themselves.